PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN COBIT 2019 PADA PT.X - STEVIE CRISTY ARTIA KUMAPE (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
PT.X is a nickel mining company. This company has utilized information technology to support its business processes, but there has been no implementation of adequate governance in achieving the company's goals. To achieve their goals, companies must synchronize the application of information technology with business goals. An information technology governance audit is needed in order to assist in evaluating the use of existing information technology in the company and to correct anything that deviates from the application of existing information technology. The framework used in this research is COBIT 2019, which was just released by ISACA, as well as analysis based on 11 design factors and with the help of the Design Toolkit. The result of this research is the design of the governance system at PT.X, which is an important process that is the main priority of PT.X. There are 8 processes generated after going through the interview and analysis stages, namely APO08 (Managed Relationships), APO12 (Managed Risk), BAI03 (Managed Solutions Identification & Build), BAI06 (Managed IT Changes), BAI07 (Managed IT Change Acceptance and Transitioning), DSS01 (Managed Operations), DSS04 (Managed Continuity), and DSS05 (Managed Security Services).